Membangun Bencana: Tinjauan Kritis atas Peran Negara dalam Kasus Lapindo - Novenanto, Anton (Masyarakat: Jurnal Sosiologi, 2015)
This article begins with the emergence and shared assumptions of the absence of the state in Lapindo case. This article aims to problematize ‘the truth’ of such assumptions. Adopting Oliver-Smith’s definition of “disasters of development,” this article argues that disaster is not just an event but also a process which can be elaborated through an examination of encompassing political agendas. Therefore, it can trigger the awareness of preventive actions prior to a disaster. The argument of the article are based on a series of critical re-reading of public documents related to the case. The result of such reading shows that the state has become one prominent actor of the incident. The state therefore has never been absent; instead, what it has done is essentially a development of a disaster. Such an argument is important in a context to add previous findings in indentifying agency of the Lapindo case so that the complexity of the case can be gradually elaborated.